2019
DOI: 10.3390/agronomy9120797
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Agronomic Biofortification of Cabbage (Brassica oleracea var. capitata) and Cowpea (Vigna unguiculata L.) Is Effective under Farmer Field Conditions

Abstract: Iodine (I) is an essential micronutrient, which plays a critical role in human metabolism. However, its concentration is known to be low in most soils, making it deficient in crops. With most I agronomic biofortification studies conducted under controlled environments, limited information currently exists on this approach of enriching I deficient crops under farmer field conditions. Two-year field experiments were conducted in 2017 and 2018 to examine efficacy of cowpea and cabbage in the uptake of foliar appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…They were conducted with the aim to prepare an I deficiency prevention program, other than through the consumption of kitchen salt based on plant enrichment with I (White and Broadley, 2009). Among the papers published within the last 15 years, there has been research on species such as kohlrabi (Golob et al, 2020), strawberry (Budke et al, 2020), lettuce (Blasco et al, 2008;Dávila-Rangel et al, 2020), basil (Incrocci et al, 2019;Kiferle et al, 2019), green bean, lettuce (Dobosy et al, 2020), cabbage, cowpea (Ojok et al, 2019), broccoli raab, curly kale, mizuna, and red mustard (Gonnella et al, 2019).…”
Section: Iodine In Plantsmentioning
confidence: 99%
“…They were conducted with the aim to prepare an I deficiency prevention program, other than through the consumption of kitchen salt based on plant enrichment with I (White and Broadley, 2009). Among the papers published within the last 15 years, there has been research on species such as kohlrabi (Golob et al, 2020), strawberry (Budke et al, 2020), lettuce (Blasco et al, 2008;Dávila-Rangel et al, 2020), basil (Incrocci et al, 2019;Kiferle et al, 2019), green bean, lettuce (Dobosy et al, 2020), cabbage, cowpea (Ojok et al, 2019), broccoli raab, curly kale, mizuna, and red mustard (Gonnella et al, 2019).…”
Section: Iodine In Plantsmentioning
confidence: 99%
“…Cabbage plants were also grown in sandy loam (pH = 5.60, OM = 3.10%, total iodine = 5.6 mg/kg), and clay (pH = 4.50, OM = 4.70%, total iodine = 1.3 mg/kg) soils using the same 5-15 g I − /ha foliar spray technology. The effect of soil on the iodine concentration of leaves was not investigated as the iodine concentrations obtained on the two soils were averaged (105 mg/kg DW) [51]. Fertilizer containing iodine (10-590 mg/kg) was applied for biofortification, and iodine concentrations of 30 mg/kg FW [34] and 160 mg/kg FW [14] were achieved in the cabbage leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Our CBA focused on two crops, i.e., cabbage and cowpea. Recent agronomic experiments in Northern Uganda demonstrated that these two widely consumed vegetables are able to accumulate iodine when applied as foliar fertilizer during production [11].…”
Section: Study Context and Participantsmentioning
confidence: 99%
“…Hence, agronomic biofortification presents a practical and feasible alternative capable of enhancing the iodine content of staple foods in the short run. Previous studies have demonstrated the efficacy of many food crops to absorb and accumulate iodine, applied as fertilizer [4,[8][9][10][11], despite also being considered relatively expensive to routinely buy and apply in rural contexts [7,12]. For example, agronomic biofortification with iron (Fe) and zinc (Zn) was found to cost between USD 376-942 and USD 311-1146 per disability-adjusted life year (DALY) saved, respectively, in China [7], whereas Zn agronomic biofortification cost an estimated USD 461-619 per DALY saved in Vietnam [13] and USD 226-574 in China [14].…”
Section: Introductionmentioning
confidence: 99%